2016
DOI: 10.1161/atvbaha.116.307182
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Lipid Genome-Wide Association Study Signal on Chromosome 18q11.2 Implicates HNF4A-Mediated Regulation of the TMEM241 Gene

Abstract: Objective We recently identified a locus on chromosome 18q11.2 for high serum triglycerides (TGs) in Mexicans. We hypothesize that the lead GWAS single nucleotide polymorphism (SNP) rs9949617, or its linkage disequilibrium (LD) proxies, regulate one of the 5 genes in the TG-associated region. Approach and Results We performed an LD analysis and found 9 additional variants in LD (r2>0.7) with the lead SNP. To prioritize the variants for functional analyses, we annotated the 10 variants using DNase I hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We processed the METSIM RNA-seq dataset similarly as described in Rodriguez et al 43 . Briefly, for the METSIM RNA-seq dataset, we isolated total RNA from abdominal subcutaneous adipose needle biopsy using the Qiagen miRNeasy kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We processed the METSIM RNA-seq dataset similarly as described in Rodriguez et al 43 . Briefly, for the METSIM RNA-seq dataset, we isolated total RNA from abdominal subcutaneous adipose needle biopsy using the Qiagen miRNeasy kit.…”
Section: Methodsmentioning
confidence: 99%
“…We filtered genes for those with expression of FPKM > 0 in more than 90% of the samples. Additional details of this dataset have been previously described in Rodriguez et al 43 . We inverse-normal transformed the FPKMs and adjusted for hidden confounding factors using PEER 46 by removing 22 PEER factors based on a cis -eQTL analysis on chromosome 20 and choosing an optimal number of PEER factors without a loss of statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, individual or multiple regulatory variants have been shown to influence allelic differences in transcriptional activity at GWAS loci for lipid traits or coronary artery disease. At an association signal for triglycerides near TMEM241 , the rs17259126-A allele showed higher transcriptional activity than the rs17259126-G allele and also stronger HNF4A protein binding [25]. The authors proposed that the rs17259126-G allele is associated with lower TMEM241 expression, leading to higher triglyceride levels.…”
Section: Allelic Differences In Transcriptional Activitymentioning
confidence: 99%
“…Rodríguez et al 16 analyzed a locus on chromosome 18 associated with high serum triglycerides in Mexicans. Using linkage disequilibrium analysis and a reporter assay, they found that the rs17259126-G allele alters expression of TMEM241 in the METSIM Cohort (Metabolic Syndrome in Men) and that reduced TMEM241 expression increases triglyceride levels.…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%
“…Using linkage disequilibrium analysis and a reporter assay, they found that the rs17259126-G allele alters expression of TMEM241 in the METSIM Cohort (Metabolic Syndrome in Men) and that reduced TMEM241 expression increases triglyceride levels. 16 Other studies further explored CAD GWAS data by working to annotate replicated CAD loci. In one such study, Ghosh et al 17 integrated large-scale GWA data with a large pathway database.…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%